(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2014)
2,4-Dichloro-pyrimidine-6-carbonylchloride (2) was synthesized by refluxing orotic acid (1) with phosphorus oxychloride and phosphorus pentachloride. Compound (2) underwent a smooth Friedel-Craft’s reaction with a number of substituted benzene to yield 2,4-Dichloro-6-aroylpyrimidines 6 and 7 which were converted to the corresponding dimethoxy pyrimidines (8, 9) on treatment with sodium methoxide in methanol. The iodination reaction on 2,4-dimethoxy-6-aroylpyrimidines (8, 9) was attempted by several methods but only NIS-TFA-TFAA method gave the desired products, 2,4-dimethoxy-5-iodo-6-aroylpyrimidine (10, 11) in good yields. Dhaka Univ. J. Pharm. Sci. 12(2): 97-102, 2013 (December) DOI: http://dx.doi.org/10.3329/dujps.v12i2.17613